2021
DOI: 10.1002/solr.202000732
|View full text |Cite
|
Sign up to set email alerts
|

Improving Performance and Stability of Planar Perovskite Solar Cells Through Passivation Effect with Green Additives

Abstract: Perovskite solar cells (PSCs) have debuted as the photovoltaic devices with the most potential and progress is being made at an unprecedented pace. Meanwhile, additive engineering is continuously pushing the power conversion efficiency (PCE) and device stability to higher levels by passivating defects and regulating crystallization behaviors. Considering the scalable fabrication of PSCs in the following stage, seeking green additives for optimizing perovskites is extremely valuable and paramount. Herein, we pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The calculated electron defect density also decreases from 1.720 × 10 16 to 1.470 × 10 16 cm −3 , respectively. 67 In short, the DPPO molecule has the capability to reduce the hole defect density, hence inhibiting defect-induced carrier recombination, as seen by the PL and TRPL measurements.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The calculated electron defect density also decreases from 1.720 × 10 16 to 1.470 × 10 16 cm −3 , respectively. 67 In short, the DPPO molecule has the capability to reduce the hole defect density, hence inhibiting defect-induced carrier recombination, as seen by the PL and TRPL measurements.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…A light-intensity-dependent J−V test was used to thoroughly evaluate the carrier recombination dynamics and charge transport process. 67 Figure 4i displays the relationship between V OC and logarithm of the incident light intensity (log I). V OC = εkT ln I/e + constant was the equation used to fit the data.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that fumaric acid not only stabilizes the [PbI 6 ] 4− framework of the perovskite crystals and efficiently passivates the surface defects, but it also improves nucleation processes to endow the perovskites with large sized grains and few GBs. 28 Pengyun et al used a green and natural cellulose derivative containing hydrogen bonds into methylammonium lead iodide (MAPbI 3 ) precursors to serve as a bi-functional additive. Consequently, the compact and pinhole-less morphology of the cellulose-treated MAPbI 3 film with large sized crystals and passivated GBs is realized.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many strategies for improving the photovoltaic performance and stability of PSCs have been reported, including mixed-halide engineering, , surface and interface passivation, additive engineering, selection of the charge-transport material, , and encapsulation . Among the aforementioned methodologies, additive engineering is considered the most effective and promising option because of the well-established intrinsic coordination ability of lead cations in the [PbI 6 ] 4– octahedral matrix of perovskites.…”
mentioning
confidence: 99%